Implementation of PID controller on revolute control of universal strech and bending machine (USBM) simplified model - Norasyikin, Julis (2008)
The aim of this project is to control DC motor position which is one component in USBM simplified model. Thus, the integral control, PID controller is used to control the position of the DC motor. Proportional-Integral Derivatives controller is widely used among the industries systems. At first stage of the project, the mathematical model of the plant, DC is derived before the PID controller is usable. The crucial part of designing the controller is tuning the three gains which are the Proportional gain, Kp, Integral gain, Ki , Derivatives gain ,KD are performed using Root-locus tuning method. The simulation of the DC motor position control is done in order to understand the PID controller. After that the controller and DC motor are interfaced using Programmable Logic Controller, PLC. Using PLC, the controller is algorithm is implemented by using ladder diagram in CX-programmer software